Estimating population abundance and monitoring population trends of endangered, elusive subterranean mammals (Rodentia: Spalacinae: Nannospalax) using HRAMN methodology - Orsolya Moldován; Szabocs Balogh; Gábor Bakó; Zsolt Molnár; Gyula Szabó; András Molnár; Attila Németh (Global Ecology and Conservation)
Monitoring rare or endangered species is vital for biodiversity conservation, but it is particularly challenging for hidden or elusive species. The subterranean Eurasian blind mole rats are such species. The newly identified endemic species of this group found in the Pannonian Basin (Central Europe) are highly threatened by extinction. Their concealed lifestyle complicates population monitoring, yet such data are crucial for their conservation. To address this problem, a new methodology called HRAMN was introduced, utilizing complex aerial cartographic surveys. The method was tested in two protected areas in Eastern Hungary, home of the endangered Hungarian blind mole rat (Nannospalax hungaricus hungaricus). HRAMN involves collecting data through aerial surveys and producing high-resolution orthophoto mosaics and digital surface models. These data allowed the identification of blind mole rat mounds and the monitoring of population trends. The HRAMN methodology proved to be a highly effective replacement for traditional full-field surveys of blind mole rat habitats. It is particularly useful for monitoring large areas, which had been previously unfeasible. However, certain limiting factors occurred in blind mole rat habitats that require field presence and control, even with the aerial imagery-based HRAMN method. Recommendations have been made to address those limiting factors that have been identified. HRAMN methodology not only enhances survey accuracy but also allows for frequent monitoring, providing unprecedented detail on the population dynamics of these rodents. Additionally, the study explored the relationship between the spatial patterns of the blind mole rat mounds and their habitats, offering deeper insights into their ecology and potentially aiding in the development of more effective conservation strategies.